On the use of options by mutual funds: Do they know what they are doing? - Gjergji Cici; Luis-Felipe Palacios (University of Cologne, Centre for Financial Research (CFR), 2013)
Using detailed options holdings, we examine how mutual funds' use of options affects performance and risk. Using options generates, on average, no performance advantages. In fact, funds that follow certain distinct strategies underperformed. The only salutary impact is lower portfolio risk for a subset of funds that buy puts for insurance. Perhaps wanting to limit additional losses, these funds also respond to poor performance in the first part of the year by reducing portfolio risk. Our findings suggest no permanent or temporary aggressive risk taking by options users, suggesting instead that some funds use options primarily for risk management.
Keywords: 330